LE « SICKNESS COUNTRY » (PARC DE KAKADU, AUSTRALIE): ENTRE MYTHE, RÉALITÉ ET MISE EN VALEUR TOURISTIQUE - ERIC FOUACHE; CÉCILE FOUACHE; CHRISTINE SYREN (Revue Roumaine de Géographie)
«Sickness Country» (Park Kakadu, Australia): between myth, reality and tourism potential. This region is found in the North Country. Aborigines from the Jawoyn tribe consider it a territory rendered sacred by their ancestor creator, God Bula. The region lies in the vicinity of Kakadu Park and is put on the UNESCO World Heritage List as Arnhem Territory. Its central part, Sickness Country, concides with the presence of a metal-bearing deposit (gold, platinium and palladium) associated with a high concentration of uranium.Mining, which goes back to the early 1880, has generated some major conflicts, being at the same time a source of radioactive pollution. Currently, the three types activity going on in the Park have led to acontradictory stance: the exploitation of uranium mine close to Jabiru Town, tourism in the Kakadu Park and Arnhem Territory. Paradoxically, the broad public has not been informed about the geological substrate. As a matter of fact, the aboriginal communities associated to the management of the Park consider that informingthe public would be incompatible with the cultural representation of landscape history expressed in the conception of the God Bula myth, namely, that any disturbance shall unlish the disease the Park is named after. The question is, whether the aboriginal population, ignorant about the radioactivity concept, may somehow be aware of the risks posed by the region, an awareness they have translated to the Bula myth. Viewing things in this way may facilitate some relationships between the rational understanding of environmental dynamics and traditional aboriginal culture, provided real inter-cultural dialog and not merely cohabitation between the two cultures is aimed at. So, when it comes to protected natural sites, the problem is to make a decision between using information, or upholding the traditional representation to boost tourism.